Case Report: A Patient Diagnosed With Miller Fisher Syndrome and Myasthenia Gravis at the Same Time - Chen, Nan; Cai, Hanyu; Cheng, Jianhua (Frontiers in Neurology, 2022)
In this case report, we describe a patient who was first diagnosed with Miller Fisher syndrome (MFS) combined with myasthenia gravis (MG). A 58-year-old male patient presented with acute dysarthria with dizziness, ophthalmoplegia, absence of deep tendon reflexes in the extremities, and ataxia. Lumbar puncture 1 week after onset showed albuminocytologic dissociation and serum antibodies against GQ1b and GT1a turned out to be positive. Ultimately, the patient was diagnosed with MFS, which is a rare variant of Guillain-Barre syndrome. Because the clinical manifestations of the patient could not exclude MG, electromyography, and serum muscle weakness antibody profile were performed. The results showed positive for axillary nerve repetitive electrical stimulation and antibodies against acetylcholine receptor (AChR) and titin were detected, so the patient was diagnosed with MG at the same time. Even though only five cases of overlapping MFS and MG so far have been described, two different autoimmune diseases may coexist. When one disease presents with uncommon symptoms, careful identification of the presence or absence of other comorbid diseases should be required.